El delito de sicariato y la imputación de sus circunstancias especìficas en el derecho penal peruano - Saenz Espinoza, Emanuel Edgar (2019)
This investigation develops the typical figure of sicariate. In this context, the concerned criminal type is analyzed attending the guiding principles of criminal law, and the main objective is to determine and explain what are the legal grounds that justify that all types of perpetrators of the crime of hired killers, provided for in Article 108-C of the Criminal Code should be susceptible to be charged for aggravating specific to that crime. The final investigation report is divided into six parts. The first is responsible for addressing the formal aspects, such as motivation, background, justification, the problem, hypothesis, objectives, as well as the materials and methods used. Part two develops the theoretical framework, highlighting in this three important chapters, which expose the topics according sicariate in Peru. On the base of what has been said above, the results and discussion are presented in third part. The fourth part discusses two practical cases in which we contrasted the results of our cause. The major findings of the research are developed in part five. Finally, the sixth part serves to present some recommendations, and an important legislative proposal to modify the crime known as Sicariate in the Peruvian Criminal Code.